PURCHASE OF FAST-FASHION BY YOUNGER CONSUMERS IN INDONESIA: DO WE LIKE IT OR DO WE HAVE TO LIKE IT? - Rokhima Rostiani; Jessica Kuron (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Introduction/Main Objectives: Fast-fashion has been contributing to growth in the fashion industry globally by shortening its life cycle and transforming the behavior of companies as well as younger consumers. Background Problems: Younger consumers are generally motivated to purchase products, especially those considered to be image-enhancing, not only externally (e.g. subjective norms and behavioral control) but also internally (e.g. intention to look good, positive attitude), yet it is unclear which motivation is the more dominant one. Novelty: This study combines two concepts, namely the theory of planned behavior that explains how internal and external motivation shapes younger consumers’ purchasing behavior, and vanity as the internal motivation that drives them to purchase fast-fashion. Research Methods: This study was conducted through an online survey of young consumers, who are active on social media, for data collection, resulting in 336 valid responses; the data were analyzed with structural equation modeling. Findings/Results: It was found that attitude was the most important determinant of the purchase intention, followed by physical vanity, the subjective norm, and perceived behavioral control. Further, perceived behavioral control also has a significant positive relationship with purchasing behavior. Conclusion: Younger consumers are more affected by their intrinsic motivation to consume fast-fashion compared to the extrinsic motivation from society. This information is useful for marketers to improve their communication strategies by emphasizing individual values that may shape positive attitudes, such as quality and comfort.